Dex modulates the balance of water-electrolyte metabolism by depressing the expression of AVP in PVN - Yang, Wenzhi; Li, Hao; Cheng, Zhongle; Lu, You; Li, Wuli; Feng, Jun; Wang, Liecheng; Cheng, Juan (Frontiers in Pharmacology, 2022)
Dexmedetomidine (Dex) is a highly selective α2 adrenergic agonist used in clinical anesthesia. Studies have shown that Dex can act on the collecting duct and reduce the body's water reabsorption, thereby increasing water discharge. However, the specific mechanism of Dex on water homeostasis remains unclear. The hypothalamus is the regulatory center of water and salt balance and secretes related neurochemical hormones, such as arginine vasopressin (AVP), to regulate the discharge of water and salt. The paraventricular nucleus (PVN) and supraoptic nucleus (SON) in the hypothalamus are also considered to be the key targets of the thirst loop. They are responsible for the secretion of AVP. The suprachiasmatic nucleus (SCN) is also one of the brain regions where AVP neurons are densely distributed in the hypothalamus. This study used C57BL/6J mice for behavior, immunofluorescence, and blood analysis experiments. Our results showed that Dex could not only depress the expression of AVP in the PVN but also reduce serum AVP concentration. The animal water intake was decreased without impairing the difference in food consumption and the urine excretion was enhanced after the intraperitoneal injection of Dex, while AVP supplementation restored the water intake and inhibited the urine excretion of mice in the Dex group. In addition, the renin-angiotensin-aldosterone system is vital to maintaining serum sodium concentration and extracellular volume. We found that serum sodium, serum chloride, serum aldosterone (ALD) concentration, and serum osmolality were decreased in the Dex group, which inhibited water reabsorption, and the plasma osmolarity of mice in the Dex group supplemented with AVP was significantly higher than that in Dex group. We also found that Dex significantly increased the concentration of blood urea nitrogen and decreased the concentration of creatinine within the normal range of clinical indicators, indicating that there was no substantive lesion in the renal parenchyma. These results showed that Dex could modulate the balance of water-electrolyte metabolism by depressing the expression of AVP in PVN without impairing renal function.